Factors Affecting the Academic Performance of Undergraduate Students' in University of Ilorin, Nigeria - OJO, Oludare David; SABA, Mamman Daniel; JAMBERLANG, Abraham Ray (International Journal of Educational Management, 2025)
The outcome of a process is very important in any enterprise. Student progress can only be measured through their academic performance. This paper examines the f actors affecting academic performance of CRS students' at the university of llorin, Nigeria. One hundred and six three hundred level (300L) students were randomly selected for this study using structured questionnaire. Data collected were analysed with descriptive and inferential statistics. Results of the study showed that teacher effectiveness, study habits, family and environmental factors and school facilities significantly predicts the academic performance of university undergraduates. It was recommended that government should fulfill its agreement with academic staff, of universities, teaching and learning resources such as internet facilities, library holdings should be provided by the school authorities and parents should provide moral and f inancial support to the children.